Central Banking and Fintech-A Brave New World? : CHRISTINE LAGARDE. (International Monetary Fund, 2017)
Address at the Bank of England Twentieth Anniversary Conference London, U.K. September 29, 2017 International Monetary Fund Managing Director Christine Lagarde delivered this address at the Bank of England conference, 'Independence-20 Years On' in London, U.K., on September 29, 2017.